Model Tata Kelola Keamanan Data pada Ekosistem Pendidikan Muhammadiyah: Sintesis ISO 27001:2022 dan Nilai PHIWM - Ady Suprayitno (Pustaka Peradaban, 2026)
Digital transformation requires educational institutions to manage data as a strategic asset to support learning and academic services, yet it simultaneously increases the complexity of security risks. Muhammadiyah, as an organization overseeing thousands of educational units, faces challenges with fragmented data security governance due to its federative organizational structure. This research aims to develop a federated data security governance model through the synthesis of the ISO/IEC 27001:2022 standard and the values of the Islamic Pedagogy of Life for Muhammadiyah Members (Pedoman Hidup Islami Warga Muhammadiyah or PHIWM). Utilizing a conceptual literature review approach with content and thematic analysis, this study examines international standards, normative organizational documents, and relevant scientific literature. The results formulate a